2020
DOI: 10.1016/j.solener.2020.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimal solar photovoltaic (PV) system for Sudan

Abstract: Highlights Finding the optimal solar PV and the best locations for the utilization of solar energy in Sudan using HOMER. Investigating the costs and emissions that would be avoided using PV instead of diesel generators. Examining the effect of solar panel price on the project economics. The optimal solar PV was determined to be Studer VarioTrack VT-65 with generic PV. The optimal location for the employment of solar en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…As per the results of previous studies, there is a negative correlation between the cost of solar energy and its public acceptance. For instance, [69] concluded that solar PV was still more costly than traditional electricity. During purchasing circumstances, consumers also think about cost details to address monetary deficits [70].…”
Section: Solar Pv Cost (Spvc)mentioning
confidence: 99%
“…As per the results of previous studies, there is a negative correlation between the cost of solar energy and its public acceptance. For instance, [69] concluded that solar PV was still more costly than traditional electricity. During purchasing circumstances, consumers also think about cost details to address monetary deficits [70].…”
Section: Solar Pv Cost (Spvc)mentioning
confidence: 99%
“…Different energy production alternatives are costly, such as building dams on the Nile, and many other options, such as diesel generators, are associated with pollution problems and adverse environmental impacts. The Sudanese government has activated an initiative to exploit renewable energy and aims to reach 38% of electricity production by 2030 and achieve 100% production by 2050 [26,27]. Sudan contains potentials for many renewable energy projects such as solar energy, wind energy, etc.…”
Section: Case Studymentioning
confidence: 99%
“…Recent developments in renewable energy systems have increase their potential for utilization in irrigation. However, the costs of renewable energy sources such as solar photovoltaic (PV) systems are considered to be high due to the high initial capital costs [21,22]. Although there are many financing opportunities being provided by Sudan's government and international organizations such as the United Nations Development Program (UNDP) to promote renewable energy for sustainable agriculture, the accurate determination of water requirements dictates the cost and viability of renewable energy options.…”
Section: Introductionmentioning
confidence: 99%